Derivation and Differentiation of Adipose-Tissue Regulatory T Cells: A Stepwise, Multi-Site Process - Sivasami, Pulavendran; Li, Chaoran (Frontiers in Immunology, 2020)
CD4+ Foxp3+ regulatory T cells (Tregs) not only enforce peripheral tolerance and restrain self-reactive immune responses, but also maintain organismal homeostasis and safeguard the function of parenchymal tissues. A paradigmatic tissue-Treg population resides in the visceral adipose tissue (VAT) and regulates organismal metabolism by interacting with adipocytes and local immunocytes. Compared with their lymphoid-tissue counterparts, VAT Tregs have a distinct T cell receptor (TCR) repertoire and transcriptional profile, allowing them to maintain and function in the unique tissue microenvironment. However, when, where, and how VAT Tregs acquire their distinct features and what signals drive their phenotypic diversification have just started to be unraveled. Here we summarize the recent advances in our understanding on the mechanisms of VAT-Treg derivation and differentiation. We discuss the origin and life history of VAT Tregs, review the identification and characterization of a VAT-Treg precursor population in the secondary lymphoid organs, and highlight a stepwise reprogramming model of VAT-Treg differentiation that involves multiple stages at distinct locations. Lastly, we discuss whether a similar process may also be involved in the differentiation of Tregs from other non-lymphoid tissues and the imperative questions that remain to be addressed.